(untitled) (UNIZIK Journal of Marketing, 2026)
This study examined the influence of digital marketing strategies on consumer behavior among adults in Abuja, FCT, Nigeria. The paper is grounded in the Theory of Planned Behavior and Technology Acceptance Model. A a cross-sectional survey of 384 consumers was conducted across Abuja Municipal Area Council, Gwagwalada, and Kuje using multi-stage stratified sampling from March May 2026. Four strategies were measured: social media marketing, email marketing, search engine marketing, and mobile advertising. Consumer behavior was operationalized as purchase intention, brand loyalty, and electronic word-of-mouth using 5-point Likert scales adapted from validated instruments.